Serial Changes in Pulmonary Function after Video-Assisted Thoracic Surgery Lobectomy in Lung Cancer Patients - Seok, Yangki; Jheon, Sanghoon; Cho, Sukki (The Thoracic and Cardiovascular Surgeon, 2014)
Background The aim of this study is to evaluate the serial changes in pulmonary function and the recovery time for the observed postoperative values to reach the predicted postoperative values after video-assisted thoracic surgery (VATS) lobectomy for lung cancer.Patients and Methods Patients undergoing VATS lobectomy for lung cancer were prospectively evaluated using complete preoperative and repeated postoperative pulmonary function tests (PFTs). The parameters of PFT at each time were compared according to the resected lobe as well as the presence of chronic obstructive pulmonary disease (COPD). The differences between the observed and predicted postoperative values of PFT and the recovery time for the observed values to reach the predicted values were calculated.Results Seventy-two patients (33 men, 39 women; mean age: 63.9 years) received complete pre- and postoperative regular PFT after undergoing VATS lobectomy. Of these patients, 24 (33.3%) patients satisfied the criteria for COPD. During the immediate postoperative period, forced vital capacity (FVC) percentage of the patients who received right lower lobectomy patients was decreased most significantly compared with the preoperative values. Compared with the upper lobectomy (UL) group, the lower lobectomy (LL) group showed a significant decrease of FVC% up to 6 months. However, there was no significant difference at 12 months after surgery. Patients with COPD showed little reduction of FEV1% that persisted significantly until 1 month after the surgery in both UL and LL groups. The recovery time was shortest in the left lower lobectomy patients, and it was shorter in the LL group than in the UL group.Conclusions Postoperative pulmonary function and recovery time were different depending on the lobe resected and presence of COPD in VATS lobectomy patients. The information obtained from postoperative serial PFT would help accurately predict postoperative pulmonary function changes and recovery time after VATS lobectomy for lung cancer.
Keywords: pulmonary function; thoracoscopy/VATS; lung cancer treatment